Evaluating the Vibrational Characteristics of Double Walled Carbon Nanotubes with Pinhole Defects - Patel, Ajay M.; Joshi, Anand Y. (Current Nanoscience, 2015)
This manuscript studies the effect of defects like large vacancies which can be categorised as pinholes, on the vibration characteristics of double walled carbon nanotubes (DWCNT). Simulations are performed on chiral, zigzag and armchair nanotubes with cantilever and bridged conditions using molecular structure mechanics approach. Pinholes are the larger vacancies (through which a C60 molecule can pass) consisting of a no. of missing atoms, which are formed during the manufacturing process. Researchers have reported that variation in the current and voltage along with a proper dose of electrons leads to development and migration of vacancies which further increases in size. In this manuscript, the authors have categorized these larger vacancies into two types i.e. 6 missing atoms and 24 missing atoms on the outer wall of DWCNT. Moreover, it has been reported by many researchers that the location of defect affects the vibrational characteristics of nanotubes. Hence considering the vibrational aspect, the effect of number of such defects and their location along the length of nanotube has been studied. The simulation results indicate that the resonant frequency of defective DWCNT is reducing with the increase in chiral angle. Further, it is also observed that the fundamental frequency reduces with the increase in the number of pinhole defects in DWCNT and maximum frequency reduction takes place when the defect is located nearer to the fixed end of DWCNT.
Keywords: molecular dynamics